GENIALLY LEARNING MEDIA BASED ON POSNER’S THEORY TO REDUCE MISCONCEPTIONS IN LINEAR MOTION - Chairatunisa, Chairatunisa; Maison, Maison; Furqon, Muhammad (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2025)
Misinterpretation of concepts or misconceptions often occurs in physics, especially in linear motion material. To overcome this problem, this study developed interactive learning media based on the Genially platform by applying Posner’s Conceptual Change Theory. The research used the 4D development model (Define, Design, Develop, Disseminate) and involved 35 grade XI students at SMAN 5 Jambi City. The novelty of this research lies in the systematic integration of Posner’s conceptual change approach and Genially’s interactive features, which have not been effectively applied in the context of high school physics learning. The results showed that the developed media was able to significantly reduce the level of student misconceptions, with an average decrease from 10.48% to 5.24%. The Wilcoxon Signed-Rank Test statistical test yielded a significance value of 0.042 (p < 0.05), indicating a significant difference between the pre- and post-treatment values. The implication of this research is the availability of alternative digital learning media that are not only engaging and in line with the characteristics of the digital generation, but also effective in addressing student misconceptions in depth. This media can also serve as a model for developing other teaching materials on complex physics topics prone to misconceptions.